Pengelolaan usaha tani bayam (Amaranthus tricolor L.) di Kota Pekanbaru - Fika Yulia Rachmah; Sukendi Sukendi; Yusni Ikhwan Siregar (Pelantar Press, 2020)
Spinach (Amaranthus tricolor L.) is a plant whose leaves are usually consumed as vegetables. The purpose of this study is to analyze spinach (A. tricolor L.) farming in an ecological, economic and social perspective and formulate sustainable spinach (A. tricolor L.) farming strategies in Pekanbaru City. The research was conducted in the city of Pekanbaru in May-July 2020. This research was conducted using the survey method to the field to obtain relevant information about the implementation of spinach farming in Pekanbaru City. The results of this study are the area of land for planting spinach in Tampan District covering 3 hectares and in Marpoyan Damai District 3.5 hectares. The type of soil used in Marpoyan Damai and Tampan Districts is humus soil. Soil pH in Marpoyan Damai and Tampan Districts ranges between 5.5-6. The average rainfall in Pekanbaru City is 170.7 with an average length of rainy days 14 days per month and humidity in Pekanbaru City is 70-85%. Overall, in terms of ecology, it is suitable for good habitat for growing spinach. Costs incurred in Marpoyan Damai District are Rp 11,670,000 per hectare while in Tampan District Rp 8,260,000 per hectare. The revenue of spinach farming group in Marpoyan Damai District is Rp. 22,800,000 and in Tampan District is Rp. 17,100,000. The income of spinach farmers in Marpoyan Damai District is Rp11,130,000 and in Tampan District Rp8,840,000. B / C ratio in Marpoyan Damai District is 1.95 and in Tampan District is 2.07. In Marpoyan Damai Subdistrict, spinach farming is carried out by the Farmer Group, namely by Mr. Mudhofir who is 39 years old with high school education. Conflicts between farmers that have occurred are land problems and have been resolved as a family. In Tampan District, spinach farming is carried out by the Baskara Jati Farmer Group, namely by 51-year-old Mr. Topan with junior high school education. Conflicts between farmers that have occurred are differences in understanding and have been resolved as a family. The management of spinach farming in Pekanbaru City has been going well, and there is already an efficiency in planting and it is said to be profitable. Based on this analysis, spinach farming in Pekanbaru City is profitable and feasible to be developed.